Stages of change profiles of offenders : exploring offenders' motivation to work on their offending problems : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Albany, New Zealand - Yong, Abigail Dawn (Massey University, 2017)
Research has highlighted the importance of the stages of change (SoC) model (Prochaska, DiClemente, & Norcross, 1992) in assessing offenders’ motivation to work on their offending problems and as a guiding framework for selecting interventions. This thesis investigated the stages of change profiles in a group of general male offenders (N = 481) before and after a Short Motivational Programme (SMP), which is a combination of motivational interviewing and cognitive behavioural material. For the first aim, distinct homogenous stage profiles that reflected the stages of change were generated by subjecting offenders’ responses on the University of Rhode Island Change Assessment Scale (URICA; McConnaughy, DiClemente, Prochaska, & Velicer, 1989; McConnaughy, Prochaska, & Velicer, 1983) to hierarchical agglomerative cluster analysis. At pre-SMP, the Ambivalent, Non-Reflective Action, Precontemplation, Preparticipation and Participation profiles were generated. At post-SMP, the same profiles were generated with the exception of the Non-Reflective Action profile. These stage profiles were consistent with profiles elicited in previous studies, and mapped well onto the SoC model. The majority of offenders were in the precontemplation stage (represented by the Ambivalent, Non-Reflective Action and Precontemplation profiles), whereas a smaller proportion were in the preparation (represented by the Preparticipation profile) and action stages (represented by the Participation profile). For the second aim, stage profiles obtained at pre- and post-SMP were then used to investigate stage movement following the SMP, by constructing a stage-transition matrix. There was evidence for offenders with different stage profiles showing different responses to the SMP, whereby a comparatively larger proportion of offenders with the Non-Reflective Action, Preparticipation and Participation profiles appeared to continue working on their offending problems or progressed to a more highly-motivated stage, compared to offenders with the Ambivalent and Precontemplation profiles. These findings indicated that there is a need for a more flexible approach to motivational interviewing to more effectively facilitate offenders’ motivation to work on their offending problems. Men with the Ambivalent and Precontemplation profiles may require further help to resolve their ambivalence towards changing, before cognitive behavioural content is introduced. For the third aim, stage profiles at pre- and post-SMP, and stage movements were examined as predictors of recidivism in three separate logistic regression analyses, controlling for salient demographic and risk variables. Men with profiles representing the precontemplation stage were less likely to reoffend compared to men with the Preparticipation profile. This study also found that men who remained in the precontemplation stage were less likely to reoffend than those who remained in the preparation and action stages. These results suggested that men with the Preparticipation profile (which represents the preparation stage) may still be experiencing some ambivalence towards changing their behaviour, thus, impacting on their readiness to change their offending behaviour. It also raised the question on whether men with the Participation profile (which represents the action stage) may be more externally motivated to change their behaviour resulting in less lasting change upon the completion of their sentences. These findings contributed to a more in-depth understanding of offenders’ stages of change, and demonstrated that these stages have important clinical implications in guiding assessment of offenders’ motivation to work on their offending problems, and tailoring rehabilitation programmes to increase treatment responsivity and improve outcomes.
Keywords: Correctional psychology; Male prisoners; Criminals; Rehabilitation; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology::Applied psychology